Optimization of pediatric CT scans in a developing country - Fotso Eddy Kamdem; Samba Odette Ngano; Clemence Alla Takam; Alain Jervé Fotue; Serge Abogo; Cornellius Lukong Fai (BMC, 2021)
Abstract Background The purpose of this study was to assess scan parameters and to propose strategies to optimize the examinations of children (from 0 to 15 years old) on adult scanners in developing countries. Methods A study was done in 2015 and 2018 on 312 pediatric patients to verify improved practices. The study of 2015 ended with proposed strategies. Dose and scan parameters were available for prospective dose analysis. These strategies were implemented in a study of 2018. Results Amount the CT examinations study in this paper, the common was head trauma (90 %). For every pediatric CT scan in 2015, a kV of 120 was used in the various hospitals. The mAs ranged from 57.75 to 283.33, slice thicknesses from 1.25 to 2.5 mm and pitch from 0.525 to 1.375 mm. In the study of 2018, implementing the strategy defined in the methodology and proposed in 2015: CTDIVol decreased by 21.27 % for children < 1 year, 31.97 % for children 1-4 years, 17 % for children 5-9 years. DLP also decreased by 25.14 %, 36.29 % and 19.85 % for children < 1 year, 1-4 years and 5-9 years respectively. Children were exposed to ionizing radiation on machines designed for adults, but now the doses received by children are reduced. Conclusions The reduction of doses during the pediatric CT examination is possible with the introduction of new optimization protocols or the acquisition of a new machine with a pediatric protocol.